2011
DOI: 10.1542/peds.2010-2294
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Dietary Botanical Supplements and Teas to Infants in the United States

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Dietary botanical supplement and tea use among infants as a separate group from children has not been studied. WHAT THIS STUDY ADDS:Our study is the first to examine prevalence of dietary botanical supplement and tea use among US infants. We found that ϳ9% of infants were given these supplements in their first year of life, although usually only for short periods. abstract OBJECTIVES:To describe the use of dietary botanical supplements and teas among infants, the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
0
20
1
2
Order By: Relevance
“…One quarter of those paired medication-NHP or NHP-NHP could have potentially caused adverse interactions, with bleeding being the most common. 9 The importance of this can be illustrated with patients taking high doses of fish oil supplements. Omega fatty acids can produce an antithrombotic effect, increasing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…One quarter of those paired medication-NHP or NHP-NHP could have potentially caused adverse interactions, with bleeding being the most common. 9 The importance of this can be illustrated with patients taking high doses of fish oil supplements. Omega fatty acids can produce an antithrombotic effect, increasing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Lack of knowledge about causes and medically appropriate treatment of URIs among parents and caregivers [5][6][7][8] has been linked to increased health service use, including pediatric emergency department (PED) visits [8][9][10] and adverse care practices such as inappropriate use of over-thecounter (OTC) cough and cold medications and/or home remedies in young children, [11][12][13][14][15] medication dosing errors, 16 and antibiotic seeking. 8,9,17 Limited health literacy affects over 90 million Americans 18 and is especially prevalent in low-income households and among minorities and people with limited English proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…7,[20][21][22] They are also at higher risk for believing antibiotics are needed for URI and for using OTC medications and home remedies for young children. 13,15,20,21,23 Previous studies have found mixed impacts of educational efforts directed at care for URIs. [24][25][26][27][28][29] These studies were primarily conducted in practice settings with predominately non-minority populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a long-term survey carried out in women from late pregnancy through their infant's first year of life, 9 % of infants were treated with dietary botanical supplements or teas in their first year of life including infants as young as 1 month. The study was conducted by the US Food and Drug Administration and the Centers for Disease Control and Prevention [9].…”
Section: Introductionmentioning
confidence: 99%